Cercanía, distancia y modos de des-alejar en la época técnica contemporánea. Reflexiones a partir de Heidegger - Xolocotzi Yáñez, Ángel (Mechane, 2022)
Reflections on the contemporary technical ages have been an important part of Martin Heidegger’s thought. The present article seeks to highlight some of these reflections that the author exposes openly from what is considered the fundamental ontology, especially in Being and Time. The intention is to demonstrate that from the existential analysis of Dasein and the modes of being of entities, perspectives are opened to think the closeness and distance that govern the so-called technical age. The text begins with a brief overview of the breakdown of the hegemony of presence in modernity, to subsequently thematize the two modes of deseverance, firstly, as a tendency towards closeness and, secondly, as the overcoming of remoteness.